2013
DOI: 10.1093/jnci/djt174
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Phospholipid Fatty Acids and Prostate Cancer Risk in the SELECT Trial

Abstract: This study confirms previous reports of increased prostate cancer risk among men with high blood concentrations of LCω-3PUFA. The consistency of these findings suggests that these fatty acids are involved in prostate tumorigenesis. Recommendations to increase LCω-3PUFA intake should consider its potential risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
202
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(214 citation statements)
references
References 45 publications
4
202
2
4
Order By: Relevance
“…Two recent studies have associated n-3 LC-PUFA status with prostate cancer (Brasky et al, 2011(Brasky et al, , 2013. The interpretation of these data has been criticized on a number of grounds including the fact that n-3 LC-PUFA intake was not monitored in these studies and, as n-3 LC-PUFA supplementation is not uncommon in cancer patients (see above), the reason for the observed association between n-3 LC-PUFA and prostate cancer cannot be established.…”
Section: Negative Reportsmentioning
confidence: 99%
“…Two recent studies have associated n-3 LC-PUFA status with prostate cancer (Brasky et al, 2011(Brasky et al, , 2013. The interpretation of these data has been criticized on a number of grounds including the fact that n-3 LC-PUFA intake was not monitored in these studies and, as n-3 LC-PUFA supplementation is not uncommon in cancer patients (see above), the reason for the observed association between n-3 LC-PUFA and prostate cancer cannot be established.…”
Section: Negative Reportsmentioning
confidence: 99%
“…The latter is a re-analysis of the study by Crowe et al (2008), which was already included in the meta-analyses. The applicant provided another publication (Brasky et al, 2013) which included a meta-analysis of nested case-control studies on the relationship between blood biomarkers of EPA and DHA (expressed as a percentage of total fatty acids) and prostate cancer.…”
Section: Risk Of Prostate Cancermentioning
confidence: 99%
“…However, the Panel notes that there is no rationale for combining the results obtained for DHA and for EPA individually in a pooled estimate. Brasky et al (2013) performed a meta-analysis of seven nested-case control studies which reported on the associations between blood biomarkers of DHA and EPA and total, low-grade and high-grade prostate cancer risk. The analysis included four of the five nested-case control studies included in the pooled estimates from Sorongon- Legaspi et al (2013) and Chua et al (2013), along with three additional studies which were not included before because they were reported to introduce high heterogeneity (Mannisto et al, 2003), for unknown reasons (Chavarro et al, 2007), or for later publication (Brasky et al, 2013).…”
Section: Nested Case-control and Case-control Studies On Blood Biomarmentioning
confidence: 99%
See 2 more Smart Citations